The Problem of Perception and the Experience of God : Toward a Theological Empiricism - Yadav, Sameer (Book collections on Project MUSE., 2015)
The central claim in this work is that there is a radical mistake in many contemporary accounts that require grounding a theological story of God's availability to us in experience in a prior general philosophical theory of perception. Instead, it is argued that the philosophical problem of perception is a pseudoproblem. The study concludes with a new reading of Gregory of Nyssa and his theology of the spiritual senses, which is free from the bewitchment of the problem of perception.